Simple fabrication of bismuth telluride used as saturable absorber for generating microsecond pulse fiber laser - Abdullahi, A. (2021)
This paper is the explanation of the development of Q-switched Erbium doped fiber (EDF) laser using Bismuth Telluride Bi2Te3 as SA. The continuous wave (CW) was then demonstrated in the EDF laser, which also shows the output is increased from 0.36 to 6.3 mW by increasing in the pump power from 15 to 147 mW. The center wavelength of 1567.7 nm with a 3dB bandwidth of 0.2 nm at pump power of 112 mW has been reported. The fabrication of Bismuth Telluride Bi2Te3 used a liquid phase exfoliation method. By adding a small piece of qualified Bi2Te3 film was incorporated among two optical fiber ferrules to produce the SA tool after the optical isolator, the generation of Q-switching pulse train in the EDFL cavity with the SA was generated starting from 61 to 112 mW pump power. The highest repetition rate of 46 kHz and the minimum pulse width of 7.8 μs are attained using Bi2Te3 SA with corresponding signal to noise ratios (SNR) of 47 dB. The high SNR values indicate the stability of both Q-switched lasers. The highest pulse energy and output power were achieved at 67 nJ and 4 mW respectively. The result shows a great potential for use in generating Q-switching pulses in the EDFL. The fabrication of both SAs is simple and cheap while the output of both Q-switched lasers is highly stable at room temperature. © 2021 IEEE.